The Effectiveness of using Special Labor Clothing on the Comfort Level of Multigravida Women Giving Birth in Parturition at Sultan Thaha Saifuddin Regional Hospital, Tebo, Jambi Province 2023 - Aprilia Murita Ningsih; Roni Rowawi; Elsa Puji Mediastuti; Bellia Loranthifolia; Ida Suryani (Sean Institute, 2026)
This study aims to determine the differences and analyze the effectiveness of the use of special maternity clothing on the comfort level of multigravida mothers in labor at Sultan Thaha Saifuddin Tebo Regional Hospital. This study uses a quantitative method with a